Pengaruh Nilai Tuka, Inflasi, Likuiditas, Dan Harga Emas Terhadap Jumlah Deposito Mudharabah Pada PT Bank Syariah Indonesia (BSI) Tbk Periode 2021-2024 - Ayyuasy Putri; Paulina Lubis; Yusuf Zaini Aprizal; Lucky Enggrani Fitri (JOURNAL OF SHARIA ECONOMICS, 2025)
Mudharabah deposits are customer investment budgets that do not conflict with sharia principles. Withdrawals can only be made at certain times, by the agreement made between the bank and the investor. This study aims to determine the effect of exchange rates, inflation, liquidity, and gold prices on the amount of mudharabah deposits at PT. Bank Syriah Indonesia (BSI) Tbk for the period 2021-2024. This study uses a quantitative approach and the type of data used is secondary data, namely from the first quarter of 2021 to the fourth quarter of 2024. The analysis method in this study uses the multiple linear regression method with time series data or time series linear regression model. The results of this study indicate that the variables of exchange rates, inflation, and liquidity do not affect the amount of mudharabah deposits at PT. Bank Syriah Indonesia (BSI) Tbk, the gold price variable affects the amount of mudharabah deposits at PT. Bank Syriah Indonesia (BSI) Tbk with a p-value of 0.0227 at a real level <0.05, and simultaneously there is an influence between the variables of exchange rates, inflation, liquidity, and gold prices on the number of mudharabah deposits at PT. Bank Syriah Indonesia (BSI) Tbk. With an R-Square value of 67.43%.